The effect of halogen bulb and light-emitting diode light curing units on temperature increase and fibroblast viability [version 1; peer review: 1 approved, 1 approved with reservations] - Trava, Georgia Memari [UNESP] (2021)
produced by halogen bulb (HAL) and light-emitting diode (LED) light curing units (LCUs) by irradiating dentin discs (0.5 mm and 1 mm thickness), and to evaluate their cytotoxic effects on fibroblast culture in the presence of dentin discs due to the increasing demand on resincomposite restorations and teeth bleaching for esthetic purposes. total of 20 bovine incisors were used to obtain dentin discs and divided into four experimental groups (n=10): HAL0.5: intensity of 470 mW/cm2 over a dentin disc of 0.5 mm; LED0.5: irradiation with LED Optilight Max (GNATUS-Ribeirão Preto, SP, Brazil) at an intensity of 1200 mW/cm2 over a dentin disc of 0.5 mm; HAL1: irradiation as in HAL0.5 but over a dentin disc of 1 mm; LED1: irradiation as in LED0.5 but over a dentin disc of 1 mm. The temperature increase was measured using a digital thermometer and the cytotoxicity was evaluated using an MTT assay with a mouse fibroblast cell line (L929). Parametric Data were analyzed by ANOVA and Tukey and non-parametric data were analyzed by Kruskal Wallis with Conover-Iman for non-parametric data (all with α=0.05). Results: A significant statistical difference was found between the groups HAL0.5 and HAL1 and both were different of LED0.5 and LED1 which presented higher temperature. All the experimental groups were different of the control group (without irradiation), and promoted reduction of cellular viability. Conclusions: HAL LCU promoted a lower temperature change in the to LED, regardless of the dentin thickness (0.5-1 mm). Both HAL and LED LCUs decreased fibroblast viability; however, LED promoted more significant cytotoxic effects.